Carbonate Slope Deposit of Bengalun River, East Kalimantan - Herman Darman (Berita Sedimentologi, 1998)
The Bengalon River is located in East Kalimantan, close to the northeastern margin of the Kutei Basin. A thick Paleogene and Neogene sedimentary package occur in this area, ranging from deep marine to fluviomarine depositional environments. This short note discusses the Early Miocene deep marine carbonates, particularly the calci-turbidite deposits.